A música regional e a constituição da identidade gaúcha: as representações do gaúcho e do pampa - Dias, Nitielle Floriano (2023)
The research contains analysis regarding symbolic interpretations held upon Rio Grande do Sul citizens through Content Analysis of regional gaúcho music. According to the theoretical contributions that ground this research, regional music mediates messages and influences in how the lifestyle of gaúchos is perceived. Moreover, it promotes means of understanding their identity. Eight regional gaúcho song lyrics were examined to assemble the main corpus of this study. With the purpose to embrace the observed representations, five categories were considered: “Impetuosity”, “Dignity”, “Rusticity”, “Conservatism” and “Hostility”. From this analysis, it is possible to argue that the representations displayed in the songs contain gaúcho traits, which build a network of reproduction and portrayal of many particularities. These singular characteristics are found in a specific area, the Brazilian Pampa. Also, it was found that beyond encouraging an identity which sustains the gaúcho as a reference, an enduring dealing with the gaúcho from the past and the commitment with masculinity are displayed too. The research shows the fabricated imagery of the gaúcho from the Campanha, which influences the elimination of many other gaúcho identities. However, the “gaúcho role model” seen in the song lyrics stimulates men to identify with it. The depictions are softened and justified by the traditionalist discourse. Therefore, this work is an invitation to reflect.